English-medium Instruction and the Information Technology Parallel in Japanese Higher Education - Bradford, Annette; Brown, Howard (International Higher Education, 2018)
As English-medium instruction expands in the higher education sector in Japan, stakeholders are experiencing frustration. However, these are not new problems; we have seen these roadblocks before in the implementation of information technology in the 1990s.